PERAN PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) DALAM PENANGANAN TINGGINYA TINDAK KEKERASAN PADA ANAK DI KABUPATEN SEMARANG - Prawita Putri, Aurelia; Hayu Dwimawanti, Ida; Puspo Priyadi, Budi (Journal of Public Policy and Management Review, 2024)
The problem of violence against children in recent years has increased significantly and has become a serious problem in Semarang Regency. The increasing problem of violence against children in Semarang Regency is becoming a serious problem even though there is already a special institution that handles and provides shelter for children who are victims of violence. The Integrated Service Center for the Empowerment of Women and Children (P2TP2A) is a service provider that provides protection, treatment and empowerment for women and children who are victims of violence. This research aims to determine the role of P2TP2A in dealing with acts of violence against children in Semarang Regency and to find factors inhibiting the role of P2TP2A in dealing with acts of violence in Semarang Regency. This research uses a qualitative descriptive method by collecting data through observation, interviews, documentation and literature study techniques. The data validity test in this research was carried out using the triangulation method. The research results show that the role played by P2TP2A Semarang Regency in dealing with violence against children is not optimal. This can be seen from elaboration regulation of P2TP2A Semarang and the theoretical analysis of Jam Ife and Frank Tesoriero that in the facilitative role in aspects of social rehabilitation and social security, problems are still found, namely slow employee response and employee unwillingness to be on the spot. Apart from that, in the educational role, there are still problems with P2TP2A Semarang Regency in carrying out outreach and not reaching remote areas. The recommendations given are to optimize services and infrastructure so that they can be reached by all the people of Semarang Regency and delegate authority to enable staff to contribute more.